Introduction of Digital Marketing to Increase MSME Product Sales (Ud. Rap Sehat) in North Padangsidimpuan District, Padangsidimpuan City - Mahmud, Amir; Samosir, Benny Sofyan; Mukhlis, Mukhlis (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2022)
This service activity aims to introduce digital marketing to increase sales of MSME products (Ud. Rap ​​Sehat) in North Padangsidimpuan District, Padangsidimpuan City. The partners of this PKM activity are UD. RAP SEHAT, is a business that is domiciled in the Padangsidimpuan Municipality area but its agricultural land is located in the South Tapanuli Regency area. UD. This SEHAT RAP has an agricultural business sector whose plant commodities are Coffee and Cloves, Owner of UD. RAP SEHAT, in this case Mr. Zul Fahri Harahap, since the beginning of starting his business, which started in the agricultural sector, has wanted to form a business system from upstream to downstream, namely not only being satisfied with his agricultural products but also reaching the stage of diversifying his agricultural products into ready-to-consume products. After the running of this business and the product has been released from UD. This SEHAT RAP is in the form of Clove Coffee (KopCeng) partners are experiencing problems in selling their products. Based on the problems faced by business owners UD. RAP SEHAT, which in this case is a partner for PKM activities, is the PKM team at Muhammadiyah University of South Tapanuli who are interested in analyzing the causes of existing problems through interviews with partners. After finding the point of the problem, a solution was found to solve the problem, in this case the introduction of web-based digital marketing which is expected to be a solution related to the low product sales from UD. RAP SEHAT in this case KopCeng. This PKM activity is carried out using the workshop method (presentation of material and training) to partner employees related to digital marketing.